2016
DOI: 10.1080/00016489.2016.1185538
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear implantation in Pendred syndrome and non-syndromic enlarged vestibular aqueduct – clinical challenges, surgical results, and complications

Abstract: Intra-operative risks of gushing/oozing and post-operative vertigo are the primary clinical issues in PS/NSEVA patients regarding CI. Nonetheless, the surgical success rate is high and the major complication rate is low; similar to studies of unselected series of CI recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 15 publications
0
14
1
9
Order By: Relevance
“…Equally important is the fact that none of the subjects in the present, SLC26A4 mutations positive cohort showed any other types of cochlear morphology than IP‐II. The clinical importance of this finding is that the IP‐II malformation does not bring with it an increased risk of “gusher” from the cochleostoma during cochlear implantation, as earlier embryological and more severe malformations may do …”
Section: Discussionmentioning
confidence: 96%
“…Equally important is the fact that none of the subjects in the present, SLC26A4 mutations positive cohort showed any other types of cochlear morphology than IP‐II. The clinical importance of this finding is that the IP‐II malformation does not bring with it an increased risk of “gusher” from the cochleostoma during cochlear implantation, as earlier embryological and more severe malformations may do …”
Section: Discussionmentioning
confidence: 96%
“…Kubo et al proposed the subdivision of postoperative vertigo into three groups: early dizziness, a continuous type of dizziness, and delayed vertigo with predominant dizziness qualities for each type . Mey et al distinguished between patients with postoperative vertigo starting 24 hours to 1 week (12.7%), 1 week to 6 months (9.1%), and more than 6 months (5.4%) . We searched for all studies reporting on postoperative vertigo quality and possible changes compared with their preoperative state to detect a further subgroup of patients that suffer an impact of cochlear implantation on their vestibular function .…”
Section: Discussionmentioning
confidence: 99%
“…1 Mey et al distinguished between patients with postoperative vertigo starting 24 hours to 1 week (12.7%), 1 week to 6 months (9.1%), and more than 6 months (5.4%). 102 We searched for all studies reporting on postoperative vertigo quality and possible changes compared with their preoperative state to detect a further subgroup of patients that suffer an impact of cochlear implantation on their vestibular function. 17,[19][20][21]23,24,[26][27][28][29][30] Hence, up to one-fourth of patients either suffer a new onset of vertigo or a change in vertigo quality after cochlear implantation.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] Despite the fact that EVA can result from various causes, most of the previous studies reporting the outcome of CI in patients with EVA have not included the genetic data. [6][7][8][9]14,15) A study by Mey, et al 16) included the results of genetic analysis but only reported the surgical outcome and complications of CI in patients with EVA. Lai, et al 17) reported the results of SLC26A4 mutations but did not compare the outcome of CI according to mutation types.…”
Section: Introductionmentioning
confidence: 99%